Infecção por Papilomavírus Humano e associação com os polimorfismos TP53 (rs1042522), GSTP1 (rs1695) e TNFA-308 (rs1800629) - Nascimento, Marcieli Borba do (2024)
Human papillomavirus (HPV) is the most common sexually transmitted infection (STI). Based on their potential to cause infection and lesions, HPV strains can be classified into high and low-oncogenic risk lesions. Although HPV is present in almost all cases of cervical cancer, it is not the sole factor involved in the development of this disease; other factors (e.g., host genetic factors) are associated with cervical cancer susceptibility, although they are less associated with HPV infection. The aim of this study was to determine the frequency of high-risk oncogenic HPV (HR-HPV) strains and the association of single nucleotide polymorphisms (SNPs) of TP53 (rs1042522), GSTP1 (rs1695), and TNFA-308 (rs1800629) with HPV infection. A case-control study was conducted with 39 HPV-infected women (case group) and 101 uninfected women (control group). Genotyping was performed for nine HR-HPV types (namely, 16, 18, 31, 33, 35, 45, 51, 58, and 66) and SNPs in the TP53, GSTP1, and TNFA-308 genes by polymerase chain reaction. Amplification products were visualized on a 2% agarose gel and photographed. Sociodemographic, behavioral, and gynecologic information was obtained using a semistructured questionnaire. The study population consisted mainly of young, white women in stable relationships with at least eight years of education and low alcohol and tobacco consumption. Among the viral subtypes, the most common strains were 16, 66, 18, 45 and 58. The AG genotype of rs1695 was the most common SNP. The A (ancestral) allele (OR=0.175; 95% CI=0.071-0.434; p < 0.001) and the AA genotype (OR=0.237; 95% CI=0.091-0.616; p < 0.003) were found to be protective factors against HPV infection. However, the G allele was characterized as a risk factor for viral infection (OR: 4.22; 95% CI 1.623-10.989; p<0.003) since it increases the risk of infection by more than 4-fold compared to the A allele. Compared with those with the homozygous genotype, women with the AG genotype have an almost 6-fold increased risk of HPV infection, which suggests that the presence of a single copy of the G allele may increase the risk of HPV infection. The results for rs1800629 showed a greater prevalence of the ancestral allele (G). For rs1042522, the G allele (arginine) was also the most common allele in both the cases and controls. However, no association, either allelic or genotypic, was observed between rs1800629 or rs1042522 and viral infection.